Transaminase-triggered cascades for the construction of complex alkaloids - Taday, Freya Frances Hughes (2021)
The natural defence mechanisms of plants often involve the use of secondary metabolites known as alkaloids. Alkaloids have been shown to act as poisons and herbicides to discourage predators or supress competition from other plants. This class of metabolite has been found to have biologically useful functions, including acting as antibiotics, anticancer agents and many more. However, synthesis of these molecules often involves the use of harsh, unsustainable methodologies.